PENGARUH PERLAKUAN PANAS QUENCHING TERHADAP LAJU KOROSI PADA MATERIAL BAJA ST 37 - Muhammad Zaki; Harlin Harlin; Imam Syofii (UNIVERSITAS SRIWIJAYA, 2021)
This study aims to determine the effect of quenching heat treatment on corrosion rates on st 37 steel material. The study was conducted at the Workshop of PT Cakra Indo Pratama Banyuasin, South Sumatra. The object of this research is the development of corrosion rates on st 37 steel with dimensions of ? 20 mm and t 8mm which are quenched at a temperature of 800-900 °C. The cooling medium used is salt water, ordinary water, air and used oil. This study uses a descriptive method where the researcher observation, retrieval of data and see what type of quenching medium is resistant to corrosion rates. The results showed that the use of used oil coolant medium was more suitable for community use because the development of the corrosion rate was relatively slower.